2017
DOI: 10.28961/kursor.v8i4.109
|View full text |Cite
|
Sign up to set email alerts
|

A Data Analysis of the Impact of Natural Disaster Using K-Means Clustering Algorithm

Abstract: Indonesia is one of the country with a lot of natural disasters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
4
0
3
Order By: Relevance
“…Nevertheless, the authors did not experiment with other clustering techniques on the same dataset for accuracy measures. Several previous studies above, such as Sadewo et al (2018), Supriyadi et al (2018), and Prihandoko and Bertalya (2016), did not validate the results of clustering on the mitigation and disaster grouping by province. In addition, the results have not yet been compared with mitigation/disaster grouping.…”
Section: Clustering Disaster-prone Areas and Mitigationmentioning
confidence: 78%
See 2 more Smart Citations
“…Nevertheless, the authors did not experiment with other clustering techniques on the same dataset for accuracy measures. Several previous studies above, such as Sadewo et al (2018), Supriyadi et al (2018), and Prihandoko and Bertalya (2016), did not validate the results of clustering on the mitigation and disaster grouping by province. In addition, the results have not yet been compared with mitigation/disaster grouping.…”
Section: Clustering Disaster-prone Areas and Mitigationmentioning
confidence: 78%
“…In addition, Yana et al (2018) found two regional clusters in Indonesia, namely prone to and not prone to natural disasters. Prihandoko and Bertalya (2016) suggested the cluster correlation between natural disasters, the number of victims, and weather conditions using k-means. efforts using k-means in a disaster mitigation study.…”
Section: Clustering Disaster-prone Areas and Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Penulis [8] menganalisis intensitas peristiwa banjir di sungai wujiang, cina selatan pada lebih 53 tahun dengan 5 indikator puncak debit, tingkat puncak, volume maksimum 24 jam, volume maksimum 72 jam dan total volume banjir, menggunakan algoritma fuzzy c-means menunjukkan bahwa tingkat banjir tinggi terjadi sejak pada tahun 1990-an di daerah aliran sungai. Pada penelitian [9] melakukan analisis clustering dampak bencana alam menggunakan algoritma k-means, hasil penelitian yang dilakukan menunjukkan bahwa kondisi cuaca bukanlah penyebab utama terjadinya bencana alam, namun kondisi geografis merupakan pemicu utama masalah bencana alam.…”
Section: Pendahuluanunclassified
“…One of the most popular and widely studied grouping methods is kmeans algorithmically simple, relatively powerful, and gives "good enough" answers to various data sets. [12].…”
Section: K-medoids Clusteringmentioning
confidence: 99%